Numerical simulation of water flow through a protective barrier pillar in underground coal mines - Galav A.; Kumar R.; Singh G.S.P.; Sharma S.K. (My University, 2025)
Seepage and sudden inrush of water in an active mine are a major concern for safety and economy of coal production. A number of underground coal mines are facing the risk of inundation hazard due to incorrect surveying and inappropriate design of protective barrier pillars. Such impending risk can create serious threat to life of the miners, machines and the mining property as a whole. Seepage creates an additional problem of water handling in daily operation whereas, the sudden inrush of water in large quantity may lead to inundation. An engineering failure of this nature makes the underground mining operation vulnerable to a catastrophe. Hence, understanding of the water flow mechanism through a barrier pillar and its influence on strength of the pillar is a prerequisite for protection against such a danger. Field experience based empirical methods do not guarantee safe performance of a barrier pillar against large water head from old water logged workings as neither they are universally applicable nor they consider all the relevant factors. In this paper, a mechanical-hydraulic coupled plain strain softening model has been studied to evaluate the water flow characteristics for different width of the barrier pillar. It analyses the water flow phenomena across the barrier pillar with sequential deformation and its influence on the mechanical strength of the barrier pillar with increasing strain and water head. The induced strain in the protective barrier pillar has potential to compromise the desired objective of the protective barrier pillar. It has been observed that water pressure acting on the protective barrier pillar increases the yield zone width in the barrier pillar. The increase in the width of the protective barrier pillar has significant impact on the seepage, as pillars became mechanically and hydraulically more stable. ©2019 Japanese Society for Rock Mechanics,